Reflective Practice in International Teaching Practicum: A Case Study of an Indonesian Pre-Service Teacher in Thailand - Acep Gafar Auliya; Neni Marlina; Nita Sari Narulita Dewi (TLEMC (Teaching and Learning English in Multicultural Contexts), 2020)
This article reports a reflective practice conducted by a pre-service teacher in an international teaching practicum in Thailand. The focuses of the study are on the aspects that she reflects and the contributions of doing reflective practice on her teaching practices during the international teaching practicum since this program provides opportunities for her to learn from and about multicultural context. This case study collected the data from a pre-service teacher's written reflection and analyzed qualitatively using thematic analysis. The results of this study revealed that the pre-service teacher reflects on some key aspects namely teaching strategies, classroom management, and socio-cultural dimension. The study also discovered that her reflective practice contributed on her teaching practices such as in providing appropriate teaching strategies based on students' needs and characteristics, eliminating classroom management issues, and raising her awareness on cultural differences between her and her students. In the end, the contribution of this study is to facilitate the pre-service teachers' development on reflective competence as a means of building teachers' professional development. Keywords : International Teaching Practicum, Pre-service Teacher, Reflection, Reflective Practice